2016
DOI: 10.3390/catal6020025
|View full text |Cite
|
Sign up to set email alerts
|

Improved Low-Temperature Activity of V2O5-WO3/TiO2 for Denitration Using Different Vanadium Precursors

Abstract: This work tested two V 2 O 5 -WO 3 /TiO 2 catalysts with different vanadium precursors for selective catalytic reduction (SCR) of flue gas NO using NH 3 at 150-450˝C. While catalyst A was prepared using ammonium metavanadate (NH 4 VO 3 ) through incipient impregnation, catalyst B was made according to the solvothermal method using vanadyl acetylacetonate (VO(acac) 2 ) as the vanadium precursor. The catalytic evaluation for denitration was in a laboratory fixed bed reactor using simulated flue gas under conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…This conclusion explains the reason why WW regeneration is more effective than thermal regeneration. In fact, the thermal treatment could only promote ammonium sulfate decomposition, which largely occurs at T < 400 • C, as also reported by Gan et al [26], whereas WW solubilized also the other more stable sulfates and easily removed ash debris poorly attached to the monolith walls. This result is roughly in agreement with data reported in Table 4 showing that only 1/3 of the total sulfates were removed through thermal regeneration, whereas with the washing treatment it was possible to remove the remaining fraction.…”
Section: Regeneration Treatmentssupporting
confidence: 77%
“…This conclusion explains the reason why WW regeneration is more effective than thermal regeneration. In fact, the thermal treatment could only promote ammonium sulfate decomposition, which largely occurs at T < 400 • C, as also reported by Gan et al [26], whereas WW solubilized also the other more stable sulfates and easily removed ash debris poorly attached to the monolith walls. This result is roughly in agreement with data reported in Table 4 showing that only 1/3 of the total sulfates were removed through thermal regeneration, whereas with the washing treatment it was possible to remove the remaining fraction.…”
Section: Regeneration Treatmentssupporting
confidence: 77%
“…Specifically, the ammonium sulfate was chemisorbed on the catalyst surface, forming a bidentate SO4 2− and interacting with TiO2, thereby creating the mutual effect [35]. For the V 2p spectra, V with a binding energy of 515.4-516.0 eV was attributed to V 4+ , and V at 516.6-517 eV was attributed to V 5+ [25]. The ratio of V 4+ /V 5+ was a crucial factor affecting the denitrification activity of the catalyst.…”
Section: Ft-ir Resultsmentioning
confidence: 99%
“…Gan et al. reported that low‐temperature deNO x activity of V 2 O 5 ‐WO 3 /TiO 2 was improved in the presence of catalyst B instead of catalyst A. Catalyst A was prepared using NH 4 VO 3 as a precursor in a conventional aqueous impregnation method whereas catalyst B was prepared using VO(acac) 2 (acac=acetylacetonate, C 5 H 7 O 2 ) as a precursor in a solvothermal method . The vanadium in VO(acac) 2 is five‐coordinate with a square‐based pyramidal geometry and vanadium is in the oxidation state +4.…”
Section: Traditional Scr Catalystsmentioning
confidence: 99%